2005
DOI: 10.1071/sh04030
|View full text |Cite
|
Sign up to set email alerts
|

The concordance of Chlamydia trachomatis genital infection between sexual partners, in the era of nucleic acid testing

Abstract: The concordance of C. trachomatis between sexual partners is in the region of 75%. This strengthens the case for epidemiological treatment for all consorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 4 publications
0
9
0
2
Order By: Relevance
“…Young age was a risk factor for concordant infection in both partners [25]. A smaller NAAT- and STD clinic-based study of 106 partnerships found 76% infection concordance [26]. A small contact-tracing study in Boston selected partnerships in which it was reasonable to infer the direction of transmission, in this case from men to women.…”
Section: Resultsmentioning
confidence: 99%
“…Young age was a risk factor for concordant infection in both partners [25]. A smaller NAAT- and STD clinic-based study of 106 partnerships found 76% infection concordance [26]. A small contact-tracing study in Boston selected partnerships in which it was reasonable to infer the direction of transmission, in this case from men to women.…”
Section: Resultsmentioning
confidence: 99%
“…When culture methods were used to diagnose chlamydia, the concordant infection rate was 24% for female index cases and 46% for male index cases; this difference was statistically significant 5. A retrospective case note review in a clinic using nucleic acid amplification tests (NAATs) to diagnose chlamydia quoted a concordant infection rate of 76%, with no significant difference between the proportion of positive male and female contacts 4. Quinn et al detected chlamydia in 68% of sexual partners of infected individuals, with no significant difference between male-to-female and female-to-male transmission frequencies 9.…”
Section: Discussionmentioning
confidence: 99%
“…Not all these chlamydia contacts will test positive for chlamydia. Results from previous studies looking at concordant infection rates for chlamydia between sexual partners have been variable, ranging from 24% to 76% 4 5…”
Section: Introductionmentioning
confidence: 99%
“…Involvement of all pelvis organs into the pathological process with high degree of probability of the adhesive changes that require the adequate correction and rehabilitation therapy is typical for the "silent" inflammatory genital organ diseases. PID is a general problem related to a wide range of disorders of female reproductive and sexual health caused by both a list of the reasons for their appearance and formation of a spectrum of complications, even after the therapy delivery [4,19].…”
Section: Etiological Factors Of Inflammatory Process Of Reproductive mentioning
confidence: 99%